Attachment and Relationship Quality Research: A Bibliometric Analysis Using VOSviewer (2015–2025) - Chi, Quang Thi Mong (Journal of Cultural Analysis and Social Change, 2026)
This study provides a bibliometric synthesis of global research on attachment and relationship quality in romantic relationships published between 2015 and 2025, situating this growing body of literature within broader social and cultural transformations of intimate life. Drawing on 890 English-language peer-reviewed articles indexed in Scopus and analyzed using VOSviewer, the study maps publication trends, geographic patterns of knowledge production and collaboration, thematic structures, and emerging research gaps. The findings indicate a marked expansion of publications after 2020, accompanied by a strong concentration of scholarly output in North America and Western Europe, while Asia, Latin America, and Africa remain marginal in global research networks. Thematic clustering reveals five dominant research domains focusing on attachment constructs, relationship quality indicators, developmental contexts, psychological processes, and methodological approaches, with attachment avoidance, relationship satisfaction, dyadic adjustment, and intimacy occupying central positions, whereas commitment and attachment anxiety receive comparatively limited attention. Despite its restriction to English-language Scopus-indexed publications, the study offers an original contribution by elucidating how geographic, cultural, and methodological asymmetries shape contemporary research agendas on intimate relationships, and by identifying critical directions for future research, particularly in relation to cultural diversity, commitment, and longitudinal and dyadic perspectives.